Improve management of acute heart failure with ProcAlCiTonin in EUrope: results of the randomized clinical trial IMPACT EU Biomarkers in Cardiology (BIC) 18 - Möckel, Martin; de Boer, Rudolf A.; Slagman, Anna Christine; Haehling, Stephan von; Schou, Morten; Vollert, Jörn Ole; Wiemer, Jan C.; Ebmeyer, Stefan; Martín-Sánchez, F. Javier; Maisel, Alan S.; Giannitsis, Evangelos (European journal of heart failure, 2019)
AIM: To determine whether initiation of antibiotic therapy (ABX) by procalcitonin (PCT) within 8 h of admission in patients presenting to the emergency department with symptoms and signs of acute heart failure (AHF) and elevated natriuretic peptides would improve clinical outcomes. METHODS AND RESULTS: The study was a randomized multicentre clinical trial conducted at 16 sites in Europe. Patients were randomized to either a PCT-guided strategy or standard care. Patients with PCT-guided strategy (n = 370) had ABX initiated if PCT was > 0.2 μg/L. Patients with standard care (n = 372) had AHF care in accordance with published guidelines without PCT. The primary endpoint was 90-day all-cause mortality. Pre-specified secondary endpoints included 30-day all-cause mortality and readmission and rate of pneumonia. The Data Safety and Review Committee recommended stopping the study for futility when 762 of the planned 792 patients had been enrolled. A total of 742 patients could be analysed. Patients were elderly (median age: 77 years), 38% were women, and had typical signs and symptoms of AHF. All-cause mortality at 90 days was 10.3% in the PCT-guided group vs. 8.2% in standard care (P = 0.316). Thirty-day readmission was significantly higher in the PCT-guided group vs. standard care but the difference vanished until day 90. The rate of pneumonia was overall low (7.5%) and not different between groups. CONCLUSIONS: In patients with AHF, a strategy of PCT-guided initiation of ABX was not more effective than a standard care strategy in improving clinical outcomes.
Gesehen am 29.10.2020